Editorial - Ndumbaro, Faraja (University of Dar es Salaam Library Journal, 2020)
Dear esteemed readers, on behalf of the editorial board and editorial committee of the University of Dar es Salaam Library Journal, I am so excited to present volume 14, issue number 2 of the journal. It gives me immense pleasure to pen down this editorial note as we are celebrating 20th Anniversary of our journal. We appreciate the intellectual generosities and contributions of all members of the editorial board and editorial committee, authors and reviewers who have contributed to this journal for the past 20 years. Your contributions are highly valued and appreciated.